2015
DOI: 10.1523/jneurosci.2998-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Histologic Substrates of Cingulate Integrity in Elders with Exceptional Memory Capacity

Abstract: This human study is based on an established cohort of "SuperAgers," 80ϩ-year-old individuals with episodic memory function at a level equal to, or better than, individuals 20 -30 years younger. A preliminary investigation using structural brain imaging revealed a region of anterior cingulate cortex that was thicker in SuperAgers compared with healthy 50-to 65-year-olds. Here, we investigated the in vivo structural features of cingulate cortex in a larger sample of SuperAgers and conducted a histologic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(163 citation statements)
references
References 72 publications
10
129
1
10
Order By: Relevance
“…Remarkably, this group of superagers exhibited full preservation of cortical thickness in several of these regions. Prior studies on the cortical neuroanatomy of superagers has called attention to the preservation of thickness of part of the cingulate cortex-a nearly identical anterior midcingulate region as we observed here (Harrison et al, 2012;Rogalski et al, 2013;Gefen et al, 2015). The comparison of superagers to typical older adults shown in Figure 1d of Harrison et al (2012) demonstrates preserved thickness in some of the other regions we found, including rostral medial PFC, anterior insula, superior frontal gyrus, and angular gyrus.…”
Section: Neural Network Integrity As a Neurobiological Substrate For supporting
confidence: 72%
See 4 more Smart Citations
“…Remarkably, this group of superagers exhibited full preservation of cortical thickness in several of these regions. Prior studies on the cortical neuroanatomy of superagers has called attention to the preservation of thickness of part of the cingulate cortex-a nearly identical anterior midcingulate region as we observed here (Harrison et al, 2012;Rogalski et al, 2013;Gefen et al, 2015). The comparison of superagers to typical older adults shown in Figure 1d of Harrison et al (2012) demonstrates preserved thickness in some of the other regions we found, including rostral medial PFC, anterior insula, superior frontal gyrus, and angular gyrus.…”
Section: Neural Network Integrity As a Neurobiological Substrate For supporting
confidence: 72%
“…All participants were required to score within 1.5 SDs of published normative values for each neuropsychological instrument on the basis of their age and education. To be designated as a superager, an elderly adult was required to meet two strict psychometric criteria similar to previous studies (Harrison et al 2012;Rogalski et al, 2013;Gefen et al, 2014). First, they were required to perform at or above the mean gender-adjusted value for young adults (age range, 18 -32) on the Long Delay Free Recall measure of the CVLT (CVLT-LD).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations